Dawoud Bey - two American projects - Bey, Dawoud 1953- (San Francisco Museum of Modern Art, 2020)
Directors' forewords / Neal Benezra and Adam D. Weinberg -- Now is the time / Corey Keller and Elisabeth Sherman -- Dawoud Bey's historical turn / Steven Nelson -- Plates: Night coming tenderly, black -- To fling my arms wide on: On Night coming tenderly, Black / Claudia Rankine -- Black compositional thought: black hauntology, plantationocene, and paradoxical form / Torkwase Dyson -- Plates: The Birmingham project -- Familiar grace / Imani Perry
Impressum: This catalogue was published on the occasion of the exhibition "Dawoud Bey: An American Project", held at the San Francisco Museum of Modern Art, February 15-May 15, 2020; the High Museum of Art, Atlanta, June 27-October 18, 2020; and the Whitney Museum of American Art, New York, November 20, 2020-April 4, 2021
Includes bibliographical references
Keywords: Bey, Dawoud -- 1953-; USA -- Motiv; Landschaftsfotografie; Person of Color -- Motiv; Porträtfotografie; Bey, Dawoud / 1953- / Exhibitions; Photography, Artistic / Exhibitions; Portrait photography / Exhibitions; Ausstellungskatalog -- San Francisco Museum of Modern Art -- 15.02.2020-25.05.2020 -- San Francisco, Calif.; Ausstellungskatalog -- High Museum of Art -- 27.06.2020-18.10.2020 -- Atlanta, Ga.; Ausstellungskatalog -- Whitney Museum of American Art -- 20.11.2020-04.04.2021 -- New York, NY; Bildband